Peculiarities of diagnostics and clinical course of different immunohistochemical subtypes of breast cancer. - El Khazhzh, M. Kh.; Bondarenko, I. M.; Aseyev, O. I.; Shponka, I. S.; Zavizion, V. F.; Sklyar, A. S.; Vinichenko, L. M.; Khodzhuzh, M. I.; Kunik, A. V.; Artemenko, M. V. (Medicni Perspektivi, 2014)
Modern global guidelines in oncology consider treatment of various forms of breast cancer according to molecular tumor subtype. Steroid receptors, epidermal growth factor receptors, p53, Ki67 proliferative activity index and others are the key indicators of aggressiveness of malignant breast tumors. The material for this study was the retrospective study of the standard set of breast cancer immunohistochemical markers (estrogen receptors, progesterone, epidermal growth factor type 2) in 8171 patients. 4 groups of patients - luminal A, luminal B, triple negative and HER2-neu positive subtypes of tumors were identified according to immunohistochemical status. We analyzed overall survival without relapse in 491 patients with breast cancer, clinical data and data of immunohistochemical studies were matched. Based on the investigation it was determined that in the early stages of the disease (1-2) luminal A subtype of cancer is often diagnosed. In the late stages the most common subtype is HER2-neu positive breast cancer. Herewith, patients with luminal A subtype of cancer have the best performance of the overall survival (OS ) (32,91±2,33 months), and the worst results were found in patients with HER2 - neu positive breast cancer (22,58±1,28 months). The data obtained determine HER2 - neu positive subtype as the most aggressive type of breast cancer, and the luminal A subtype – as the least aggressive one.